Dedicated to the 80th anniversary of the doctor of biological sciences, academician of the Academy of Ecology, professor Mamutov Zheken Umbetkulovich (Journal of Geography and Environmental Management, 2019)
Dedicated to the 80th anniversary of the doctor of biological sciences, academician of the Academy of Ecology, professor Mamutov Zheken Umbetkulovich